Efficacy And Safety Of Apatinib Treatment In Platinum-Resistant Recurrent Epithelial Ovarian Cancer: A Real World Study - Zhang J; Li A; Jiang Q; Zheng F; Zhu H (Dove Medical Press, 2019)
Jindi Zhang,1,2,* Anyang Li,2,* Qi Jiang,2 Feiyun Zheng,2 Haiyan Zhu1,2 1Department of Gynecology, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, Pudong, Shanghai 200126, People’s Republic of China; 2Department of Gynecology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haiyan ZhuDepartment of Gynecology, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, 2699 Gaoke West Road, Pudong, Shanghai 200126, People’s Republic of ChinaTel +86 137 5846 5255Email zhuhaiyandoc@sina.comObjective: To evaluate real-world use and outcomes of apatinib treatment in platinum-resistant recurrent epithelial ovarian cancer.Methods: This is an observational study. Patients with platinum-resistant recurrent epithelial ovarian cancer initiating apatinib treatment from January 2016 to December 2018 were included. The primary end point was progression-free survival. Other end points included overall survival, objective response rate, disease control rate, and toxicity.Results: A total of 28 platinum-resistant epithelial ovarian cancer patients were enrolled in this study. Thirteen cases received apatinib as maintenance therapy following chemotherapy with a median progression-free survival of 6.0 months and a medium overall survival of 11.0 months. Four patients received apatinib as palliative following chemotherapy with 2 cases in progressive disease and 2 cases in stable disease. Eleven cases received apatinib alone as salvage therapy with a disease control rate of 81.8% and a median progression-free survival of 3.0 months. The most common adverse effects were hand-foot syndrome (53.57%), secondary hypertension (46.43%) and fatigue (14.29%). Five patients discontinued treatment due to grade 3 toxicities and 4 patients required dose reduction because of adverse effects.Conclusion: Apatinib produced moderate improvements in progression-free survival in patients with platinum-resistant epithelial ovarian cancer both as maintenance therapy following chemotherapy and as single-agent salvage therapy. Our study suggests that apatinib may be effective for women with platinum-resistant recurrent epithelial ovarian cancer.Keywords: epidermal growth factor receptor, apatinib, ovarian cancer, platinum-resistant, maintenance therapy